(3LRA ajg KeGfhf MOjkKG Yf KeGfjI TjNkGs - (3CHh HcQ eMeO Hf GdMSf Hf YHO GdMSjf Hf YHO Gddg GdBLQj,J (B360 (3g` s
(3ChdgG (B:s
(3CNHQfG GdTjNGf GdaGVd TgGH GdOjf CMeO Hf GdTjN GdEeGe GdYdGeI TeS GdOjf eMeO Hf EHQGgje hCbVi GdbVGI aNQ GdOjf Hf eMeO Hf CMeO GHf eMeO gHI Gddg GdSjhWi s
(3BNQgG (B:s
(3hjbhd (B: (3Ef Gddg YHGOkG djShG HCfHjGA hdG TgOGA jZHWge GdfHjhf hGdTgOGA hai Gdbhe QLd CYGQHi , aHM GdQcHJg Ke bGd (B: (3jG QShd Gddg MOKfG s
(3Vef eLehY , JQJjHgG (B: (3ef U (B279 - (3U(B286s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B97 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B243s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B140 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B523s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs